COMMUNITY PREPAREDNESS: A MULTIDISCIPLINARY APPROACH TO PUBLIC HEALTH IN SOUTHERN CONNECTICUT - Szatkowski, Ryan (My University, 2013)
The Naugatuck Valley Health Department (NVHD) of Seymour, Connecticut, is the official public health entity for its participating communities. Those employed with NVHD are committed to improving the quality of life for all served through the promotion of health, prevention of disease, and ensuring a safe and clean environment for all. Projects facilitated during field experience hours at NVHD aimed to implement community preparedness strategies through disaster and bioterrorism response outreach, food safety promotion, senior citizen emergency planning, and radon awareness. Field experience work, discussed in this report, demonstrates applied knowledge and skill performance in the five core competencies of public health: biostatistics, environmental health, epidemiology, health services administration, and social and behavioral sciences, as well as the public health emphasis area of food safety and biosecurity. As a culminating experience, the Naugatuck Valley Medical Reserve Corps (NV-MRC) was created to supplement existing emergency response procedures during times of natural disaster, or intentional attack. A three year strategic plan, complete with five specific objectives, was developed to grow and strengthen the NV-MRC as a vital community preparedness and response organization. Hurricane Sandy was a natural disaster that provided an opportunity to deploy the NV-MRC and later assess and evaluate the NV-MRC response strengths and weaknesses.
Keywords: Public Health; Community Preparedness; Connecticut; Public Health (0573)